KONTRIBUSI EXPERIENTIAL MARKETING STRATEGY PADA LOYALITAS PENGUNJUNG OBJEK WISATA-WISATA DI ROKAN HULU - Hidayat, Afrizal (Jurnal Ilmiah Cano Ekonomos, 2015)
This study examines the loyalty of visitors in Rokan Hulu consisting of four objects that Hapanasan, Cipogas, Hot Suaman and Aek Martua.Focused in this study is to explore the contribution of experiential marketing strategy antribut loyalty visitor is using deslriptif quantitative methods and sample collection that visitors encountered during tourist location study with 100 primary responden.Data of distributing questionnaires to the respondents using a Likert scale and further descriptive analysis and path analysis or path analysis. The results of research that can that attribute experiential marketing strategy consisting sense variable (X1), feel (X2), think (X3) directly no significant effect on loyalty (Y), but the act variable (X4), and relate (X5) direct significant effect on loyalty (Y). From the findings in this study, the researchers suggest Rokan Hulu Government should pay attention to the existing tourist attraction, especially in the location of this research to develop tourist facilities and infrastructures and services be improved for tourist visitors. If it is addressed, it will provide a good impression so that there will be an attitude of loyalty of the tourist visitors.